Toxicity profile of standardized Krishna Vajra Abhraka bhasma made from biotite mica - Vijaya Anil Pandit; Sharwan Kumar Singhal; Gourav Bharat Deshmane; Ranjana Ajit Sahasrabuddhe; Manjiri Neelkanth Karandikar; Madhuri Sadashiv Pawar; Vishakha Sumant Kulkarni; Jayshree Shriram Dawane; Asmita Ashish Wele (Journal of Ayurveda and Integrative Medicine)
Introduction: The Bhasmas, herbo-minerals, are reported to produce adverse effects when used clinically. Therefore, the present study aimed to assess the safety of Krishna Vajra Abhraka Bhasma (KVB), through acute and subacute toxicity testing. Materials and Methods: After ethics committee approval, total 66 Wistar albino rats weighing 180–200 gms were used. Experiments were conducted as per CCSEA guidelines. In acute toxicity study, a single limit dose of 2000 mg/kg of KVB with honey was administered to six female rats. Subacute toxicity studies involved 60 Wistar albino rats of either sex, randomly divided into six groups and received KVB in low (highest clinical dose extrapolated to rats), medium (double the low dose) and high (double the medium dose) dose administered orally for 28 days. Results: No mortality or adverse effects on rat's general behaviour or internal organs was observed in acute toxicity study The results of subacute study indicated no significant differences in body and organ weights, hematological or renal function between control and treated groups. However, mid and high doses of KVB revealed reversible, dose-dependent hepatotoxicity through biochemical and histopathological evaluation, while the satellite high dose group did not exhibit this effect, confirming it as drug-induced hepatotoxicity. Conclusion: The acute toxicity results positioned KVB in class V (safe) of the GHS classification. Subacute toxicity findings suggested that while low therapeutic doses were non-toxic, mid and high doses induced reversible hepatotoxicity, emphasizing the importance of careful dosage considerations and patient monitoring in Ayurvedic practice. The study contributes valuable insights into the safety profile of KVB, addressing concerns for both users and practitioners of Ayurvedic medicine.